Practicing information literacy: perceptions of LIS working students on navigating the workplace setting and its information practices - Bautista, Chloie G.
Information literacy (IL) exists within various contexts, each requiring a slightly different set of IL skills to effectively manage information within the specified information environment. This study explores the translation of IL skills from academic to workplace contexts based on the lived experiences of Library and Information Science (LIS) working students of UPSLIS. The study makes use of LIS students’ technical knowledge of IL to obtain the essence of WIL as a phenomenon as perceived from the information science perspective. Utilizing the transcendental phenomenology approach, semi-structured interviews guided data collection among four respondents that led to the identification of several themes, grouped according to the research objectives: understanding the concept of WIL, its application in professional practice, and the perceived challenges in practicing WIL.